Was ist und was braucht ein bedeutender Finanzplatz? - Reinhard H. Schmidt; Michael H. Grote (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2005)
In this paper, we first discuss the notion of 'important financial centres' and the socioeconomic and political conditions which need to be fulfilled for such a centre to exist. We then address the issue of the so-called 'end of geography' which has attracted a lot of attention recently. Under this suggestive title some authors have recently advances the proposition that specific locations lose their role as economic centres and are more and more replaced by so-called virtual centres. We do not suscribe to this view since, as we argue in our paper, we do not agree that proximity has lost much of its importance in the financial business. However, the provocative proposition rightly directs attention to the really important question of how competition plays out in this area. We therefore analyse which kind of competition is relevant in the case of financial centres and how it affects the position of Frankfurt in the international hierarchy of financial centres. Our proposition is that 'horizontal competition' such as that between Frankfurt and Paris is not really relevant, and much less relevant than 'vertical competition' between Frankfurt and London as the main centre in Europe on the one hand, and Frankfurt and different local subcentres in Germany on the other. That is, Frankfurt must fear to lose business to London and/or to the We conclude with a set of observations on how the role of Frankfurt as a financial centre can be strengthened.
Keywords: R11; G15; 330; financial centres; economic geography; Frankfurt; regional competition; Finanzplatz; Standortfaktor; Standortwettbewerb; Regionale Konzentration; Deutschland; Grossbritannien; Gruppe Deutsche Börse Frankfurt; Main; International Stock Exchange of the United Kingdom and the Republic of Ireland London